Casein Phosphopeptide and Diode Laser in Treating Dentin Hypersensitivity: A Clinical Study: CPP and diode laser for dentin hypersensitivity - Faheem, Sanam; Qasim, Rimsha; Kumar, Chander; Farooqui, Waqas Ahmed; Rehman, Anam; Maqsood, Shahida; Sahito, Muhammad Amin; Kumar, Naresh; Zafar, Muhammad Sohail (Journal of Lasers in Medical Sciences, 2025)
Introduction: Dentin Hypersensitivity is a clinical condition in which a patient experiences intense, short-duration pain. This research aims to determine the effectiveness of Casein phosphopeptide amorphous calcium phosphate paste (CPP-ACP) used alone or combined with a diode laser in treating dental hypersensitivity. Methods: One hundred and twenty patients were enrolled in this randomized, double-masked clinical trial based on specific inclusion and exclusion criteria screened at the Department of Periodontology at Dow Dental College, Dow University of Health Sciences, Karachi. They were randomly assigned to one of four treatment groups: Group I: CPP-ACP paste, Group II: Diode laser only (for 100-150 seconds, on 980nm/0.5-1W laser 19J/cm), Group III: CPP-ACP paste with diode laser, Group IV: Placebo treatment. To assess pain intensity, discomfort (botheration), and tolerance, the Visual Analog Scale (VAS) was used. Patients rated their experiences on a scale from 0 to 10, with higher scores indicating greater severity. For statistical analysis, a twoway ANOVA test was applied to assess the mean difference within groups after considering the normality of data distribution. A P-value of<0.05 was considered significant, indicating a meaningful difference between treatment effects. Results: All treatment groups showed a significant reduction in VAS pain, botheration, and tolerance, with consistent improvement. The laser-only group (Group II) showed consistent improvement, with the most crucial change occurring immediately after the treatment among variables of VAS pain, botheration, and tolerance. Conclusion: Diode laser therapy appears to be the most effective treatment for managing dental hypersensitivity. However, combining CPP-ACP with a diode laser is also a viable option depending on individual patient needs and preferences. Trial Registration: ID: NCT06463938. https://clinicaltrials.gov/study/NCT06463938. Name of the trial registry: A Clinical Trial to Compare Lasotronix Alone or in Combination With CPP-ACP to Treat DH. Registration date: 2024-05-12